2019
DOI: 10.1097/sla.0000000000002664
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Change Over Time After Hepatectomy for Colorectal Liver Metastases

Abstract: The impact of genetic, surgery-related, and clinicopathologic factors on OS and CS3 changed dramatically over time. Specifically, BRAF mutation status dominated prognosis in the first year, whereas positive surgical margins and resected extrahepatic disease determined prognosis thereafter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 45 publications
5
60
2
2
Order By: Relevance
“…Moreover, data regarding tumor biology such as the mutation status of KRAS, NRAS, BRAF and others is lacking. This might substantially influence the analysis, as was recently shown by others . Beyond These faults, our data may support the assumption that in the modern era of CRLM treatment, an aggressive surgical attitude, in combination with multiple line systemic therapy, may prolong patient's lives, even if an R0 resection cannot be achieved.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, data regarding tumor biology such as the mutation status of KRAS, NRAS, BRAF and others is lacking. This might substantially influence the analysis, as was recently shown by others . Beyond These faults, our data may support the assumption that in the modern era of CRLM treatment, an aggressive surgical attitude, in combination with multiple line systemic therapy, may prolong patient's lives, even if an R0 resection cannot be achieved.…”
Section: Discussionsupporting
confidence: 81%
“…This might substantially influence the analysis, as was recently shown by others. 19,20 Beyond These faults, our data may support the assumption that in the modern era of CRLM treatment, an aggressive surgical attitude, in combination with multiple line systemic therapy, may prolong patient's lives, even if an R0 resection cannot be achieved. As long as the surgical risk in a given case is acceptable, and a complete macroscopic resection, leaving the patient with "no evidence of disease" is feasible, it may be worthwhile to offer surgery, even if an R0 is not realistic.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This implies that wild‐type tumors have a benign biologic behavior that justifies such an approach. However, a recent study by the author's group questioned the prognostic importance of KRAS mutational status and its use as the only variable to inform surgical management . Employing a conditional survival analysis, we found that the impact of KRAS on survival appeared moderate at best and comparable with that of traditional clinicopathologic factors (CEA levels, lymph node metastasis, or multiple tumors).…”
Section: Resultsmentioning
confidence: 67%